Transglutaminase‐catalyzed amination of pea protein peptides using the biogenic amines histamine and tyramine. (26th October 2016) - Lu, Xinyao; Hrynets, Yuliya; Betti, Mirko
Abstract: BACKGROUND: Biogenic amines (BAs) are produced by the enzymatic decarboxylation of amino acids, and are well‐known for their toxicity to humans. This study describes a new method using microbial transglutaminase (MTGase) to covalently link BAs such as histamine (HIS) and tyramine (TYR) to the glutamine residues of alcalase‐hydrolyzed pea protein (PPH). RESULTS: The incubation of PPH and HIS and TYR in the presence of MTGase at 37 °C led to the formation of conjugates, as determined by liquid chromatography, after derivatization with dansyl chloride. Seventy‐six % of HIS and 65% of TYR were covalently incorporated to PPH by MTGase. The incubation of PPH and TYR in the presence of MTGase exhibited a 52% DPPH radical scavenging activity at 10 mg mL −1 . Conjugation via MTGase improved the antioxidant status by reducing lipid peroxidation. CONCLUSION: This study emphasizes that the application of MTGase can effectively reduce histamine and tyramine content while simultaneously enhancing antioxidative capacity of PPH. © 2016 Society of Chemical Industry